The effect of paclobutrazol and prohexadione-calcium on lodging resistance and yield of rice (orvza sativa l.) - Sri Wahyuni,; Sinniah, Uma Rani; Yusop, Mohd. Khanif; Amarthalingam, Rajan (2001)
MR 219 rice plants were treated with Paclobutrazol and Prohexadione-calcium as a foliar spray at panicle initiation stage. Results showed that application ofthese chemicals retarded internodes and culm length. .increased diameter of rice stem and stem breaking resistance, leading to increase lodging resistance. The application of the growth retardants did not effect yield